Revision of an academic library user experience survey. Issue 1 (4th February 2019) - Aksu Dunya, Beyza; De Groote, Sandra
Abstract : Purpose: The purpose of this paper is to explain how an academic library's Student Experience Survey was revised and improved based on available research on survey design methodology and piloting efforts. Thus, it aims to contribute existing literature on library assessment and survey methodology by addressing issues of planning and coordinating assessment. The paper also provides a guideline on the survey revision process for existing instruments. Design/methodology/approach: The library assessment coordinator collaborated with Assessment Coordinator Advisory Committee (AC2) to revise and improve the survey. The revision process started with adding suggested items and constructing new items based on library assessment planning survey administered to library faculty previously. Regular monthly meetings were held with the committee to facilitate the revision process. Multiple facets of the survey implementation were revised including wording, content, order and format of the items, response scales and survey distribution. Each facet was addressed based on available research on survey methodology and cross-checked with the committee members. Findings: The revised 2018 University of Illinois at Chicago (UIC) Libraries Student Experience Survey consists of a total of nine items with response matrices, single choice response format and open-ended response format to measure students' satisfaction, need and their use of the various library resources and services. The changes made to the survey are grouped into three categories: wording and content, response categories and scaling and design, font and layout. The revision process of the UIC Libraries Student Experience Survey can serve as an example for academic or other types of libraries that wish to track and report their impact regularly. Originality/value: The UIC Libraries Student Experience Survey provides evidence that careful revision and piloting as well as obtaining relevant stakeholder buy-in to the process lead to build effective survey tools.